Riverbed-material texture and composition of Bishnumati River, Kathmandu, Nepal; implications in provenance analysis - Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2009)
The Bishnumati River, a major tributary of the Bagmati River in the Kathmandu Basin, is a low-gradient, low-sinuosity river with a short high-gradient head. The tributaries contributing the Bishnumati River supply sediments from granite-gneiss sources located towards the north of the river area, and from sedimentary rocks of the Phulchoki Group from the northwest and the west of the Bishnumati watershed. Four representative segments each from third, fourth, fifth and sixth order stretches were sampled and analysed for riverbed-material size, and gravel shape and composition, to characterise riverbed materials, to understand downstream distribution of shape, size and composition of sediments, and to understand provenance of riverbed materials. The D50 of the segments 1, 2, 3 and 4 are 25.11 mm, 0.871 mm, 3.75 mm and 27.86 mm, respectively. The riverbed materials are classified as Gravel, muddy sandy Gravel and muddy Gravel, which are very poorly sorted indicating textural immaturity. Gravels are compact bladed in form. Oblate prolate index (OPI) shows more oblate nature of gravels from downstream segments (sixth order stream). Gravels have high settling sphericity (0.6-0.8) and slightly higher flatness index (0.51-0.54). They are subrounded to rounded although there exist some angular to well rounded gravels. Downstream changes in shape parameters are not remarkable perhaps because of short distance of transport, insufficient abrasion, or durability of gneissic and granitic clasts, or quick transport of gravels during floods. Shape also seems to be influenced more by inherited properties of parent rocks. The gravels from sedimentary rocks increase from the upstream to downstream sites of the river at the expense of reduction of gneissic and granitic gravels. Existence of siltstone and sandstone gravels in the fifth (Segment 2) and forth order (Segment 3) mainstreams is remarkable as there is no primary parent source upstream of these segments. Existence of sedimentary gravels shows local provenance (fluvio-deltaic terrace deposits) and perhaps suggests existence of paleodrainage system different from the present doi: 10.3126/bdg.v12i0.2250 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 55-62